Perjalanan Syaikh Ahmad Khatib dalam Melahirkan Tokoh Pergerakan dan Pendidikan Islam di Nusantara - Nurachman, Azhar; Anshori, Isa (Lembaga Yasin AlSys, 2024)
This article will discuss a Nusantara scholar who became a Grand Teacher in Mecca, contributing to the emergence of figures in the Islamic movement and education in Nusantara, namely Syaikh Ahmad Khatib Al Minangkabawi. It will explore his journey to becoming a significant scholar in Mecca, along with his various students, particularly those from Nusantara. Furthermore, it will delve into his influence on the thoughts of independence movements among his Nusantara students and the scholarly impact he had on the renewal and Islamic education in various regions of Nusantara. Lastly, the article will highlight his renowned and influential works in the Islamic movement and education in Nusantara.